Triflic-acid-catalyzed tandem allylic substitution–cyclization reaction of alcohols with thiophenols—facile access to polysubstituted thiochromans - Abdul Sadeer (2019)
Hitherto inaccessible multisubstituted thiochroman derivatives were constructed via the one-pot reaction of thiophenols with allylic alcohols catalyzed by 0.2 equiv triflic acid under metal-free conditions. A variety of thiochroman derivatives can be obtained by this straightforward protocol that allows the introduction of up to four substituents at various locations on the thiochroman skeleton. Relative conformations of all isolated products were confirmed by NOESY NMR studies, and a stepwise mechanism, proceeding via an allylic substitution-intramolecular cyclization protocol, is proposed on the basis of NMR experiments.